Rating physical fitness versus autonomic heart rate regulation in runners - Krivoruchenko, E. V.; Ivanov, A. I.; Shadrina, O. V.; Sentizova, M. I. (Theory and Practice of Physical Culture, 2020)
Issues of physicality tests (including the physical fitness and cardiovascular system performance tests) in sprint and middle-distance running have always been given a high priority, although remain still underexplored. The study was designed to analyze the HR/ cardiographic data and training process test data to find correlations of the physical fitness versus the autonomic heart rate regulation in sprinters and middle-distance runners. Sampled for the study were the Class II to CMS qualified sprinters (with the below-average physical fitness rates) with equal representation (50%/ 50%) of the sympathotonic and vagotonic types of autonomic heart rate regulation; and the highly skilled (MS) runners with above-average physical fitness rates and with 100% of those tested with the sympathotonic type of autonomic heart rate regulation. The highly-skilled middle-distance runners sample included those with the above-average-physical fitness subsample with the equally represented (50%/ 50%) the sympathotonic and vagotonic types of autonomic heart rate regulation; and the high-physical fitness subsample with 100 % of those tested with the vagotonic type of autonomic heart rate regulation. We used a heart rate variability analysis to classify the sprinters and middle-distance runners performance rates. The study data and analysis may be helpful for the coaching teams when making corrections to the individual training systems.